Healthcare innovations from marine biodiversity: from drug discovery to disease prevention - Kumar Jaiswal, Vinay; Srinivasa Rao, Varri (Journal of Neonatal Surgery, 2025)
Marine biodiversity has emerged as a rich resource for innovative solutions in healthcare, offering promising avenues for drug discovery and disease prevention. This paper explores how marine organisms, with their unique bioactive compounds and adaptations, contribute to the development of novel therapeutics and preventive strategies for various diseases. From anticancer agents to antimicrobial compounds, marine biodiversity is proving to be a valuable asset in addressing unmet medical needs. Additionally, advancements in marine biotechnology are paving the way for sustainable and eco-friendly approaches to healthcare innovations. This study reviews recent research and highlights the potential of marine-derived products in transforming healthcare practices. The exploration of marine biodiversity not only expands the pharmaceutical toolkit available for healthcare but also addresses the urgent need for novel solutions to combat emerging health threats, such as antimicrobial resistance and novel viral outbreaks. This paper underscores the immense potential of marine-derived compounds in fostering a new era of innovative, environmentally-conscious, and effective healthcare solutions.